GAMBARAN TINGKAT KEPUASAN PASIEN BERDASARKAN SERVICE QUALITY TERHADAP PELAYANAN PETUGAS PENDAFTARAN DI PUSKESMAS JAGAPURA KABUPATEN CIREBON PADA TAHUN 2026 - ⁠Ica Syahidatun Nisa; Elfi; Totok Subianto; Maula Ismail (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Public Health Centers (Puskesmas) as primary healthcare facilities play an important role in providing quality health services to the community. One of the initial service points that influences patient satisfaction is the registration service. Patient satisfaction is an indicator of healthcare service success and is influenced by service quality, which includes the dimensions of tangible, reliability, responsiveness, assurance, and empathy. This study aims to describe the level of patient satisfaction based on service quality dimensions toward the services provided by registration staff at Jagapura Public Health Center, Cirebon Regency, in 2026. This study employed a descriptive quantitative method with a cross-sectional design. The sampling technique used was non-probability sampling with an accidental sampling method. The research instrument was a questionnaire using a 1–4 Likert scale. The research variables included respondent characteristics (name, gender, age, and occupation) and the five dimensions of service quality (tangibles, reliability, responsiveness, assurance, and empathy). Data were analyzed using univariate analysis to obtain frequency distributions and percentages for each satisfaction indicator.